Standards and Classification of Information Representation and Levels of Virtuality in the Medium of Extended Reality: Towards a Taxonomic Model of an XR Paradigm - Rubio Tamayo, José Luis; Gértrudix Barrio, Manuel (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Extended reality is one of the technologies that are gaining importance in the current context as it enables an enormous degree of interaction with the digital environment and information. One of the fundamental factors of this highly complex medium is the study of its visual and immersive features. From this arises the need to establish a series of information representation standards, taking into account factors such as the degree of virtuality or iconicity (level of representation), trying to establish the bases for the development of an XR Paradigm exportable to other dimensions.